Efforts to Improve Activeness and Learning Outcomes of Integrated Social Sciences Through Time Token Type Cooperative Learning Model - Agus Herianto; Nurjannah Nurjannah; Mahsup Mahsup; Sintayana Muhardini; Ibrahim Ibrahim; Eka Fitriani (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This research aims to improve the activeness and results of integrated IPS learning by implementing a cooperative learning model of Time Token type (TITO). This type of research is class action research with the subject of the study is grade VII students MTs Nurul Masak in school year 2019/2020. Research was carried out in three cycles, each cycle was carried out with 2 actions and consisted of 4 stages namely planning, implementation, observation, and reflection. The population and samples in the study were grade VII students of MTs Nurul Masakin. The research instruments used in the implementation of this action research were observations, interviews, and field notes as well as tests of students' learning outcomes on each cycle. This study used two forms of data analysis, namely quantitative analysis and qualitative analysis. Quantitative data were obtained from the percentage of students' activities in participating during the learning process and student learning results and qualitative data were used to describe data in the form of numbers in order to provide a clear picture of the activities and learning results that had been done. Based on the results of the study it showed that there was an improvement in Integrated Social Science learning outcomes using the Method of Cooperative Learning Type Time Token (TITO) which was the average value gain that each cycle increased. In Cycle I the average value obtained was 6.5, while in cycle II the average gain value reached 7.40 and in cycle III, the average value reached 8.18.